2020
DOI: 10.1002/smi.2972
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and psychological distress in cancer survivors: A systematic review and meta‐analysis

Abstract: Emotion regulation may affect the levels of psychological distress of cancer survivors, but inconsistencies exist among studies regarding the direction of this effect. The systematic review and meta‐analysis sought to estimate the associations between emotion regulation patterns (repression, suppression, experiential avoidance and cognitive reappraisal) and psychological distress among cancer survivors. Fifteen studies met inclusion criteria for systematic review, and seven studies focussing on suppression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 80 publications
0
17
1
1
Order By: Relevance
“…The structure models could be suitable for both boys and girls. Previous studies revealed that over-suppression of negative emotion may be harmful to the relief of negative emotions and lead to more behavioral problems and physical diseases, especially in females (63,64). In our study, almost of adolescents are in the early stage of adolescents, psychological and behavioral differences between boys and girls haven't appeared particularly significance.…”
Section: Invariance Of the Modelcontrasting
confidence: 51%
“…The structure models could be suitable for both boys and girls. Previous studies revealed that over-suppression of negative emotion may be harmful to the relief of negative emotions and lead to more behavioral problems and physical diseases, especially in females (63,64). In our study, almost of adolescents are in the early stage of adolescents, psychological and behavioral differences between boys and girls haven't appeared particularly significance.…”
Section: Invariance Of the Modelcontrasting
confidence: 51%
“…Up to 50% of survivors experience impaired pulmonary function [13]. Between 11 and 44% of survivors report psychological distress and depression post-treatment, and these are often severe enough to require intervention [14]. As a result of tobacco exposure, survivors of lung cancer have an increased risk for smoking-related comorbidities, including chronic obstructive pulmonary disease and cardiovascular disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high survival rate of vulvar cancer patients [ 58 ], quality of life, sexuality and psychological well-being are key areas for investigation, along with the long-term consequences of the disease and treatment pathways. These areas are crucial not only due to the high prevalence of psychological distress among cancer patient but also due to the consequences of such disorders on overall health [ 59 ]. In fact, considering breast cancer, a much more widespread, well-known and well-studied type of cancer among women, a large volume of literature is available on quality of life [ 60 ], sexuality [ 61 , 62 ] and partner relationships [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%